2013
DOI: 10.5489/cuaj.193
|View full text |Cite
|
Sign up to set email alerts
|

Review of the efficacy and safety of cryoablation for the treatment of small renal masses

Abstract: Purpose: Small renal masses are increasingly being discovered incidentally on imaging for another reason. The standard of care of these masses involves excision by open or laparoscopic techniques. Recently, ablative techniques, such as radiofrequency ablation (RFA) and cryoablation, have taken a more prominent role in the treatment algorithm of these masses. We evaluate the effectiveness and safety of cryoablation to treat renal tumours.Methods: A review of the literature was conducted. There was no language r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Ideally, ablative treatment should be compared with partial nephrectomy (PN) in a randomized and prospective setting. Nephron-sparing surgery in multiple renal cancer: a case report for Adverse Events grading system [14]. Sprenkle et al reported complications rate of 13% approximately as well [15].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, ablative treatment should be compared with partial nephrectomy (PN) in a randomized and prospective setting. Nephron-sparing surgery in multiple renal cancer: a case report for Adverse Events grading system [14]. Sprenkle et al reported complications rate of 13% approximately as well [15].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In Europe, an estimated 84 400 new cases of renal cell carcinomas are diagnosed each year with more than 60% of these being T1a tumors, thus amenable for nephron-sparing surgery. [3][4][5] The current gold standard for treating SRMs is partial nephrectomy (PN) as stated by both European Association of Urology and American Urology Association.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to oncological outcome, CA is generally considered less effective compared to radical nephrectomy or PN. 1,[5][6][7][8][9][10] However, direct comparison of the 2 modalities is difficult due to selection biases and confounding. In addition, long-term data are still very sparse when it comes to CA and PN.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave ablation and high-intensity focused ultrasound have also been trialled but are less widely available. Data regarding these emerging modalities is diffi cult to interpret because of lack of pre-procedural biopsy confi rming a malignant lesion, wide variability in the defi nition of oncological outcomes and lack of long-term follow-up (Kapoor et al 2013 ). Both RFA and cryoablation can be performed percutaneously under imaging guidance or laparoscopically.…”
Section: Focal Therapymentioning
confidence: 99%